Strong Reciprocity and Human Sociality - Herbert Gintis (University of Massachusetts, Department of Economics, 2000)
Human groups maintain a high level of sociality despite a low level of relatedness among group members. The behavioral basis of this sociality remains in doubt. This paper reviews the evidence for an empirically identifiable form of prosocial behavior in humans, which we call 'strong reciprocity,' that may in part explain human sociality. A strong reciprocator is predisposed to cooperate with others and punish non-cooperators, even when this behavior cannot be justified in terms of extended kinship or reciprocal altruism. We present a simple model, stylized but plausible, of the evolutionary emergence of strong reciprocity.
Keywords: 330